Manipulating Nonclassicality via Quantum State Engineering Processes: Vacuum Filtration and Single Photon Addition. Issue 1 (20th November 2019) - Malpani, Priya; Alam, Nasir; Thapliyal, Kishore; Pathak, Anirban; Narayanan, Venkatakrishnan; Banerjee, Subhashish
Abstract: The effect of two quantum state engineering processes that can be used to burn a hole at vacuum in the photon number distribution of quantum states of radiation field is compared using various witnesses of lower‐ and higher‐order nonclassicality as well as a measure of nonclassicality. Specifically, the modification in nonclassical properties due to vacuum state filtration and a single photon addition on an even coherent state, binomial state, and Kerr state are investigated using the criteria of lower‐ and higher‐order antibunching, squeezing, and sub‐Poissonian photon statistics. Further, the amount of nonclassicality present in these engineered quantum states having enormous applications in continuous variable quantum communication is quantified and analyzed by using an linear entropy‐based entanglement potential. It is observed that all the quantum states studied here are highly nonclassical, and the hole‐burning processes can introduce/enhance nonclassical features. However, it is not true in general. A hole at vacuum implies a maximally nonclassical state (as far as Lee's nonclassical depth is concerned), but a particular process of hole burning at vacuum does not ensure the existence of any particular nonclassical feature. Specifically, lower‐ and higher‐order squeezing are not observed for photon‐added and vacuum filtered even coherent states. Abstract : The nonclassical properties associated with two different quantum state engineering processes have been compared with a specific focus on the nonclassicality witnesses and measures.